2017
DOI: 10.1002/app.44872
|View full text |Cite
|
Sign up to set email alerts
|

Dual antibacterial functional regenerated cellulose fibers

Abstract: N-[3-(dimethylamino)propyl]methacrylamide monomer was used to impart dual antibacterial functionality to regenerated cellulose fibers. In this regard, the monomer was grafted onto the surfaces by a "grafting from" technique, then the tertiary amine groups were quaternized and the acyclic amide groups were halogenated. Antibacterial activities of the mono-and dual-functional coatings were comparatively evaluated. All the treatments were found to be effective against Staphylococcus aureus and Escherichia coli wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…These compounds can significantly differ their chemical structure—they may be aliphatic, aromatic, may contain Cl, Br or I and various other substituents, which affects both physical and chemical properties as well as their biologic activity and durability [ 24 ]. It has been reported that N -halamine polymers exhibit strong antimicrobial activity against a broad spectrum of the pathogens dangerous for human: Gram-positive and Gram-negative bacteria, fungi as well as viruses [ 24 , 26 , 27 , 28 , 29 , 30 , 31 ]. In addition, the observed biocidal properties are strong and thus the required contact time is very short (less than five minutes) [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds can significantly differ their chemical structure—they may be aliphatic, aromatic, may contain Cl, Br or I and various other substituents, which affects both physical and chemical properties as well as their biologic activity and durability [ 24 ]. It has been reported that N -halamine polymers exhibit strong antimicrobial activity against a broad spectrum of the pathogens dangerous for human: Gram-positive and Gram-negative bacteria, fungi as well as viruses [ 24 , 26 , 27 , 28 , 29 , 30 , 31 ]. In addition, the observed biocidal properties are strong and thus the required contact time is very short (less than five minutes) [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sound and heat insulations are provided by nonwoven products in the automotive industry; in addition to these properties, the flame retardancy property is demanded due to protection standards . Although there are several methods to obtain functional textiles, general methods could be separated into three sections: (1) direct production of textile materials from high‐performance polymers, (2) providing functionality by coating high‐performance polymer onto the conventional fabrics, (3) addition of organic or inorganic compounds into the fabric during manufacturing or finishing processes . The second method is most preferred method to obtain multifunctional fabrics, because it is economical and safe for human health.…”
Section: Introductionmentioning
confidence: 99%
“…The mainly used biocidal compounds include N ‐halamines ( N ‐chloramines and N ‐bromamines), quaternary ammonia salts, and heavy‐metal ions . N ‐halamines are famous and widely used biocidal groups since they are broad spectrum, rechargeable, very stable, and highly efficient .…”
Section: Introductionmentioning
confidence: 99%